2022
DOI: 10.1002/advs.202202556
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Generation of Circulating and Mucosal Decoy Human ACE2 using mRNA Nanotherapeutics for the Potential Treatment of SARS‐CoV‐2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) can cause lethal pulmonary damage in humans. It contains spike proteins on its envelope that bind to human angiotensin‐converting enzyme 2 (hACE2) expressed on airway cells, enabling entry of the virus, and causing infection. The soluble form of hACE2 binds SARS‐CoV‐2 spike protein, prevents viral entry into target cells, and ameliorates lung injury; however, its short half‐life limits therapeutic utilities. Here, synthetic mRNA is engineered to enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Currently available intramuscularly administered vaccines induce circulating memory T cells, but not lung-resident, spike protein-specific T RM responses (35,74), highlighting an advantage of our mucosal PACE-mRNA delivery strategy. Although inhaled mRNA has been investigated for prophylactic therapeutics or decoy treatments to fight SARS-CoV-2 (48,(75)(76)(77)(78), this work is important because it describes de novo induction of protective immunity against SARS-CoV-2 with intranasal delivery of a nonviral vector mRNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available intramuscularly administered vaccines induce circulating memory T cells, but not lung-resident, spike protein-specific T RM responses (35,74), highlighting an advantage of our mucosal PACE-mRNA delivery strategy. Although inhaled mRNA has been investigated for prophylactic therapeutics or decoy treatments to fight SARS-CoV-2 (48,(75)(76)(77)(78), this work is important because it describes de novo induction of protective immunity against SARS-CoV-2 with intranasal delivery of a nonviral vector mRNA vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Sahay’s group recently developed a liver-targeting LNP to deliver mRNA for SARS-CoV-2 . The mRNA encodes a soluble form of human angiotensin-converting enzyme 2 (hsACE2), which is the target for SARS-CoV-2 spike protein and mediates the endocytosis of SARS-CoV-2 into human airway cells. , The LNP composition was same to the formulation of Onpattro.…”
Section: Organ-specific Lnp By Intravenous Administrationmentioning
confidence: 99%
“…The human ACE2 is composed of three regions, namely, extracellular, transmembrane, and intracellular segments, among which the extracellular part contains a peptidase domain that participates in binding to the SARS-CoV-2 RBD [53]. The binding of S-glycoprotein to ACE2 is the initial step in the entry, replication, and subsequent pathogenesis of SARS-CoV-2.…”
Section: Ace2 Is Also a Promising Approach For The Treatment Of Covid...mentioning
confidence: 99%
“…In another approach, lipid nanoparticles were used to deliver transcribed messenger RNA into the mammalian cells to rapidly express ACE2. Different analyses revealed that the produced ACE2 was able to bind to the RBD of SARS-CoV-2 in mouse lung cells and strongly inhibited (more than 90%) the infection with SARS-CoV-2 pseudovirus [53]. However, the production of rhACE2 in human cells is a time-consuming and expensive process.…”
Section: Ace2 Is Also a Promising Approach For The Treatment Of Covid...mentioning
confidence: 99%
See 1 more Smart Citation